EFFECT OF CREATIVITY ON STUDENT LEARNING ACHIEVEMENT - Ukhty Lutfiani (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
This article is based on the various problems experienced by students in the aspect of learning achievement, many students experience learning difficulties which are influenced by internal and external problems, so that a new innovation is needed that can affect student learning achievement to be better. As for things that can improve student learning achievement is having creativity in learning so that creativity can have an effect on student achievement, therefore this article will discuss the effect of creativity on student achievement, both internal creativity in students and creativity that is influenced. other thing. This article was written to determine the effect of creativity on student achievement in terms of supporting literature.